El papel de la orientación y la confianza en las compras electrónicas en la predicción del comportamiento de compra impulsiva: Un estudio basado en miembros de la Generación Y en la India; Role of e-shopping orientation and trust in predicting impulsive buying behaviour: A study based on members of Generation Y in India - Annie John; Jain Mathew; Sridevi Nair (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2024)
– Impulse Buying and the drivers of similar consumer behaviours have captured the interest of researchers for quite some time now. The construct was first explored in the context of offline or brick and mortar stores. However, with the growing popularity of online retail stores has led to the concept being included in studies on customer behaviour, specifically in the online context. In the current study, the researchers attempt to contribute to literature on customer behaviour in the online environment by exploring the relationship between E-Shopping Orientation, Trust and Impulsive Buying Behaviour. The focus of the currents study is the members of Generation Y. The scope was limited to this specific section, given that each generation differs from the other in terms of their behaviour, needs and drivers. While the direct impact of E-shopping Orientation on Impulsive Buying Behaviour was found to be not statistically significant, the indirect effect was found to be significant. This suggests that Trust fully mediates the relationship between E-Shopping Orientation and Impulsive Buying Behaviour. In addition to contributing to literature in the area of customer behaviour, the findings also add to our understanding of a major section of the Indian customer base.
Keywords: M31; L81; 330; Shopping orientation; e-retail; Trust; Impulse Buying; Impulsive Buying Behaviour; Generation Y